0774 Factors Associated With The Continuous Use Of Psychotropic Treatments For Narcolepsy. (27th May 2020) - Ohayon, M M; Krystal, A D; Black, J; Shapiro, C M; Sullivan, S; Swick, T J; Wells, C C
Abstract: Introduction: Narcolepsy is a debilitating disorder characterized by excessive sleepiness and cataplexy episodes. There is no cure for this disease. Current treatments focus on controlling the symptoms with CNS stimulants for sleepiness and antidepressants and/or CNS depressants for cataplexy. This study examines the factors that can contribute to the cessation of narcolepsy treatment. Methods: The study includes 291 narcoleptic individuals who were interviewed twice, approximately five to seven years apart, in Wave 1 (W1) and Wave 2 (W2). Telephone interviews were conducted with the help of the Sleep-EVAL system; narcolepsy individuals were initially evaluated and diagnosed by a Sleep Specialist. Results: At W1, 49.2% of narcoleptic individuals were taking a CNS stimulant; at W2, 37% of narcoleptic individuals were taking a CNS stimulant. The use was chronic (i.e., present at W2 and W1) for 52.7% of the W2 subjects. CNS depressants were used by 19.1% at W1 and 17% at W2. Of the W1 subjects, 67.6% still reported using CNS depressants at W2. In terms of antidepressants, 38.6% and 29.6% of subjects reported using these medications at W1 and W2 respectively. Of those taking antidepressants at W2, 58.9% reported chronic use (ie, were also on antidepressants at W1). At least one of the aforementioned medication classes was used by 72% of participants at W1 and 56.1% at W2. Chronicity of nocturnal awakenings (RR: 2.7), the frequency of cataplexy episodes (RR: 2.3) and the chronicity of hypnopompic hallucinations (RR: 2.8) were associated with long-term use of narcolepsy treatment. Conclusion: Narcolepsy treatments are mostly taken to long term. Some narcoleptics individuals were able to reduce or stop treatment either because the intensity of symptoms decreased or because they developed coping mechanisms to deal with the symptoms. Support: NIH (R01NS044199), the Arrillaga Foundation and Jazz Pharmaceuticals Inc.